A socio-demographic study of the “loss to follow–up in TB cases under DOTS” in and around tertiary teaching care hospital - Pasha, M. A. M.; Fatima, Afsar; Gopichand, Sumana; Sushma, M. (International Journal Of Community Medicine And Public Health, 2017)
Background: India had 2.6 million cases of Tuberculosis as per the latest count and ranks 14th among 22 high TB burden countries globally. Loss to follow-up is a TB patient who did not start treatment or whose treatment was interrupted for 2 consecutive months or more. Knowing the demographic profile and reasons for non-adherence to treatment among the loss to follow up TB cases helps in prevention of infection source, development of resistant strains and also helps in reducing relapse rate and mortality, which helps in achieving the end TB strategy. Methods: The aim of this study was to know the socio-demographic profile of “loss to follow up in TB cases under DOTS” in and around tertiary teaching care hospital. A retrospective analytical study was done after getting a sample size i.e.79 cases from the register obtained from Tuberculosis unit, Government Hospital, Nandyal. Results: Out of 79 cases, 45 (57%) belonged to upper lower class (IV), 15 (19%) belonged to lower class (V), 14 (17.7%) belonged to lower middle class (III), 5 (6.3%) belonged to upper middle class, according to modified Kuppuswamy classification. Conclusions: The study showed that most of the patients belonged to upper lower class and there was significant association between (a) socio-economic status and symptoms appeared, (b) socio-economic status and investigations done, (c) socio-economic status and the person who diagnosed first, (d)socio-economic status and under whose supervision treatment was taken.